Financial Behavior of the Japanese Firms: Before and After the US Lehman Shock - Tsuji, Chikashi (Archives of Business Research, 2015)
This paper studies the financial behavior of the Japanese firms by focusing on, in particular, its difference before and after the US Lehman shock. Findings derived from our analyses are summarized as follows. First, (1) regarding the financial condition in Japan, after the US Lehman shock, the current ratio, the debt ratio, the capital adequacy ratio of the Japanese firms clearly improved. In addition, (2) the fixed assets ratio of the Japanese firms also clearly decreased after the Lehman shock. Further, (3) as to the state of investments, after the Lehman shock, the equity investments of the Japanese firms increased whilst the investments in bonds and real estates as well as the capital investments of the Japanese firms decreased. Keywords: Financial behavior; Financial ratio; Japanese firms; Lehman shock